Evaluation of an empiric antibiotic regimen in pediatric oncology patients presenting with fever does not reveal the emergence of antibiotic resistance over a 12-year period - Tristan Knight; Avanti Gupte; Kristopher Dulay; Robert Mitchell; Hossein Salimnia; Zhihong Joanne Wang (Elsevier, 2020)
Purpose: Neutropenic fever in a pediatric oncology patient necessitates emergent initiation of efficacious broad spectrum antibiotics. We have utilized cefepime+/-vancomycin in this context for over two decades, and sough to evaluate the efficacy of this combination at our institution and, if necessary, to identify an optimal alternative regimen. Methods: Blood culture isolates from pediatric oncology patients were reviewed over 12 years. Antibiotic susceptibilities for all unique isolates were analyzed via minimum inhibitory concentration breakpoints and interpretive categories as per the Clinical and Laboratory Standards Institute M100/M45 manuals. Percentage susceptibility was calculated, antibiograms generated, and intraspecies antibiotic susceptibility comparisons made. Billing data was analyzed to identify the number of oncology patients admitted for fever during this interval. Results: 697 unique isolates were identified: 188 Gram-negative and 509 Gram-positive (155 Gram-positive and 343 total isolates, excluding coagulase negative Staphylococcal (CONS) species). Cefepime and meropenem each covered 95.7% of tested Gram-negatives. Stenotrophomonas (Xanthomonas) maltophilia was the most resistant Gram-negative organism; no antibiotic covered all Gram-negatives. No antibiotic offered significantly improved coverage compared to cefepime. 96.0% of total tested Gram-positives were vancomycin-susceptible (including all CONS); resistant organisms included Enterococcus faecium and Enterococcus faecalis. Linezolid did not offer significantly improved coverage, while daptomycin did. Including and excluding CONS, 46.3% and 72.5% of total Gram-positive isolates were cefepime-sensitive. Blood cultures were positive in 33.7% of admissions. Central venous catheters were routinely utilized in this patient population. Prophylactic antibacterial agents were not utilized. Conclusions: Cefepime+/-vancomycin remains efficacious as first-line empiric therapy for febrile neutropenia, with notable minor exceptions. Unit-specific surveillance of antibiotic resistance is warranted to ensure ongoing appropriate empiric antibiotic usage.